Optimal capital taxation for time-nonseparable preferences - Sebastian Koehne; Moritz Kuhn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study optimal capital taxation in a dynamic Mirrleesian model with time-nonseparable preferences. The model covers the widely used cases of habit formation and durable consumption. Time-nonseparable preferences change labor supply incentives across time and thereby generate novel motives to distort capital accumulation decisions. We decompose intertemporal wedges (implicit capital taxes) into three components and provide conditions under which intertemporal wedges are positive. We derive a recursive formulation of constrained efficient allocations and evaluate the quantitative importance of habit formation for intertemporal wedges. In our baseline parameterization, habit formation reduces average intertemporal wedges by about 40 percent compared to the time-separable case.
Keywords: D82; E21; H21; 330